2016
DOI: 10.1161/circresaha.115.306799
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the (Pro)renin Receptor as a Novel Regulator of Low-Density Lipoprotein Metabolism

Abstract: T he (pro)renin receptor [(P)RR] has been implicated as a receptor for renin/prorenin (denoted as [pro]renin)-stimulated signaling, and plays a role in local renin-angiotensin system activation by nonproteolytically activating bound prorenin. 1 In experimental assays (pro)renin-(P)RR signaling results in extracellular signal-regulated kinase 1/2 (Erk1/2) activation, and as a consequence upregulation of profibrotic factors, such as transforming growth factor β, collagen, and fibronectin. [2][3][4][5][6] However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…However, the binding affinity of this receptor for renin and its precursor prorenin was found to be in the nanomolar range, while their in-vivo levels are many orders below this range, even during DRI treatment [43, 44]. On this basis, combined with the fact that the (pro)renin receptor is now additionally known to be an accessory subunit of vacuolar H + -ATPase, displaying multiple effects that are entirely unrelated to renin and/or prorenin, e.g., with regard to cardiomyocyte autophagy [45], polyuria and renal acid-base regulation [46], and LDL metabolism [47], this idea is now being abandoned [48]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the binding affinity of this receptor for renin and its precursor prorenin was found to be in the nanomolar range, while their in-vivo levels are many orders below this range, even during DRI treatment [43, 44]. On this basis, combined with the fact that the (pro)renin receptor is now additionally known to be an accessory subunit of vacuolar H + -ATPase, displaying multiple effects that are entirely unrelated to renin and/or prorenin, e.g., with regard to cardiomyocyte autophagy [45], polyuria and renal acid-base regulation [46], and LDL metabolism [47], this idea is now being abandoned [48]. …”
Section: Discussionmentioning
confidence: 99%
“…The discovery of the (pro)renin receptor [8] caused a lot of excitement, but recent studies have revealed that its in-vivo function in reality is largely, if not entirely, proreninindependent [25][26][27]. The discovery of the (pro)renin receptor [8] caused a lot of excitement, but recent studies have revealed that its in-vivo function in reality is largely, if not entirely, proreninindependent [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies questioned the physiological relevance of these findings, since in reality, prorenin concentrations are many orders of magnitude below the levels that are required to interact with this receptor, even during treatment with RAS blockers [38]. Indeed, the (pro)renin receptor has now also been linked to functions beyond the RAS [39]. To what degree its concentrations vary in relation with salt intake still needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%